Model Sistem Informasi Penilaian Rekan Satu Kelompok Secara Kolaboratif Untuk Pembelajaran Berbasis Proyek - Adi Suryaputra Paramita (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Project-based learning is one of the learning models that is currently considered suitable for Engineering-based study programs, where in project-based learning it is expected that students can produce a product that can be prepared through a collaborative process. The resulting product certainly needs to be assessed at the end of the semester, in this learning model it is hoped that the assessment process will also be carried out collaboratively, so that the research process can be carried out properly and comprehensively, it is necessary to create an integrated information system model that can adopt these needs. The information system is also a solution during the COVID-19 pandemic, which causes not all lecturers to meet and gather in one place, with this information system assessment can be done online without the need to meet physically. This information system is built based on web and mobile applications, making it easier to access without any geographical and location restrictions. The result of this research is an Information System model for a collaborative assessment process for project-based learning that can be accessed from anywhere.